The Role of Nutrient Intake and Social Determinants in Anemia among Pregnant Women at Lampung Malaria Endemic Areas - Dian Isti Angraini (Faculty of Medicine, Public Health, and Nursing, 2023)
Anemia in pregnancy is a health problem, associated with an increased risk of morbidity and mortality during childbirth. The study’s purpose was to determine the role of nutrient intake and social determinants on anemia in pregnancy in the Pesawaran district. This study was an analytic observational study using a cross-sectional design, conducted in malaria-endemic areas, Pesawaran district, Lampung, from June to Desember 2021. The sample was 75 pregnant women in second trimester, taken by purposive sampling technique. Anemia was measured by examining haemogobins, data on education, family income, age, and parity were obtained from interviews, maternal knowledge using questionnaires, and food intake using a 2x24-hour food recall questionnaire. Data were analyzed univariate, bivariate, and multivariate. The results showed that anemia in pregnancy was 42,7%. Most of the pregnant women are poorly educated (50,7%), have poor knowledge (64%), sufficient income (53,3%), multiparous (68%), good age (64%), inadequate energy intake (72%), inadequate protein intake (58,7%), and inadequate iron intake (56%). The results showed that education (p=0.003), knowledge (p=0.015), income (p=0.009), parity (p=0.004), age (p=0.004), energy intake (p=0.02), protein intake (p = 0.025), and iron intake (p=0,031) has a role on anemia in pregnancy. The factors that most play a role are education, income, parity, and iron intake.